2021
DOI: 10.1111/jac.12559
|View full text |Cite
|
Sign up to set email alerts
|

Multiple‐generation seed maturity effects on seedling vigour in a production environment

Abstract: Maturity is not only critical for vigour and other seed quality characteristics but also impacts the subsequent plant performance. If these impacts on the subsequent plant are long lasting, the potential to produce vigorous, mature seed may also be affected.This scenario lends itself to the concept of seed maturity memory (SMM) -an understanding of how seed maturity may impact subsequent generations of plants and the vigour of the seeds with different maturity they produce. This study aimed to assess the exist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 36 publications
(46 reference statements)
1
0
0
Order By: Relevance
“…An increased seed maturity level (measured by a lower level of chlorophyll fluorescence (CF) of the pericarp) showed a positive effect on emergence of spinach seedlings. This is in accordance with previous studies that described a positive effect of seed maturity on the germination potential for many plant species, including spinach (Jalink et al, 1998;Deleuran et al, 2013;Song et al, 2021). The data from the 15 seed lots sown in the control substrate showed that, under optimal temperature and moisture levels, larger spinach seeds had higher emergence incidence than smaller seeds.…”
Section: Seed Traits In Relation To Seedling Emergence In the Absence...supporting
confidence: 92%
“…An increased seed maturity level (measured by a lower level of chlorophyll fluorescence (CF) of the pericarp) showed a positive effect on emergence of spinach seedlings. This is in accordance with previous studies that described a positive effect of seed maturity on the germination potential for many plant species, including spinach (Jalink et al, 1998;Deleuran et al, 2013;Song et al, 2021). The data from the 15 seed lots sown in the control substrate showed that, under optimal temperature and moisture levels, larger spinach seeds had higher emergence incidence than smaller seeds.…”
Section: Seed Traits In Relation To Seedling Emergence In the Absence...supporting
confidence: 92%